Do Empowerment and Trust Improve Organizational Citizenship Behavior (OCB)? - Suhardi, Eka; Novita, Lina; Suharyati, Henny; Herfina, Herfina; Bon, Abdul Talib (JURNAL AL-TANZIM, 2024)
This research aims to find ways to strengthen teacher OCB by analyzing the relationship between empowerment and trust. The research method uses quantitative methods with correlation analysis and SITOREM design. The research sample consisted of 104 permanent foundation teachers with instruments consisting of teacher OCB, empowerment, and trust. Data collection began with observations, interviews, and Discussion group forums to find factors influencing OCB, data analysis and processing using SEM-PLS. The research results show a positive and significant relationship between empowerment and trust in Teacher OCB with a correlation coefficient of ry12 = 0.775. The coefficient of determination value r2y12 = 0.601. The results of SITOREM's analysis of the empowerment variable show that there are indicators that must be a priority for improvement, namely competence (capabilities, professionalism). Meanwhile, other empowerment indicators are maintained and continue to be developed. Furthermore, for the trust variable, the indicators that must be improved are open communication between employees and leaders, and other trust variable indicators must be maintained and developed. It can be concluded that empowerment and trust can influence teacher OCB.